(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research investigates the most common urinary tract infection bacteria and their susceptibility to antibiotic disc and parsley (Aquas and methanol) extracts. The urinary tract microbial were isolated from patients of urinary tract infection (UTI) pregnant women patients from Baghdad Hospital. The pathogenic organisms were collected, cultured and identified. 50 microbial isolate wasset as, E. coli 56 (46.66%), Staphylococcus aureus19 (15.8%). Proteus mirabilis 6 (5%) and Klebsiella pneumonia 3 (2.5%). The pathogenic bacterial showed various zone of sensitivity to different antibiotics. Within the parsley Antimicrobial activity ranged from 3 to 20 mm. Antibacterial activity of parsley extract (5- 22) mm on UTI isolated pregnant women and methanol extracts was between (3-15) mm. Therefore, Parsley extract had a pharmacological to treat all of 50 isolates that were identify from patients. In conclusion, the findings suggested that different extractsmay content as a broad-spectrum bactericidal factor, to control the emergent pathogens any way of their drug resistance mechanismsto treat urinary tract infections